Summer School “History and Video Games”: Design, Results and Conclusions - Mugueta Moreno, Íñigo (Clio. History and History Teaching, 2018)
This study tries to show the design, results and conclusions of the Summer School “History and video games” that took place between August 28th and September 1st of 2017 at the Universidad Pública de Navarra. This Summer School was the culmination of several educational workshops focused on historical strategy videogames which were conducted in different courses of primary and secondary education. We tried to develop a teaching experience in a context outside the school. A specific teaching experience in which researchers always had control and were always free to act through the whole didactical process. Once the didactic strategies were finished and the different surveys were answered by the students, we had two main goals. On one side, we wanted to analyse the degree of credibility that these students gave to the historical contents of these video games. On the other side, we wanted to analyse if these video games gave our students an advantage to accomplish the competences of historical thinking.
Keywords: videogames; Learning; Historical thinking; History; Teaching